The prehistoric burial sites of Northern Ireland - Welsh, Henry (Archaeopress archaeology., 2014)
Much has been written about the history of Northern Ireland, but less well-known is its wealth of prehistoric sites, particularly burial sites, from which most of our knowledge of the early inhabitants of this country has been obtained. This work brings together information on all the known sites in Northern Ireland that are in some way associated with burial.